2017
DOI: 10.3103/s1067821217060165
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Zinc Ferrite Decomposition in Electric Arc Furnace Dust by Lime

Abstract: Изучены научные основы пирометаллургической технологии переработки пылей электросталеплавильного производства, содержащих ферриты цинка. Выполнен термодинамический анализ разложения феррита цинка известью. Анализ полученных расчетных данных показал, что для разложения более чем 90 % ZnFe 2 O 4 необходимо добавить к пыли не менее 46 % CaO, а для разложения более чем 95 % ZnFe 2 O 4-не менее 60 % CaO. Результаты расчетов проверены экспериментально на лабораторной печи. Экспериментальная прокалка пыли на воздухе … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…To improve the efficiency of the utilization of zinc resources, it is essential to focus on the development of technologies for the recovery of zinc-containing dust. Many investigations have reported that zinc ferrite could be decomposed by hightemperature roasting with the addition of lime [29,[35][36][37]. The recovery of zinc from synthetic zinc ferrite by calcium roasting and ammonia leaching was reported in our previous paper [38].…”
Section: Introductionmentioning
confidence: 81%
“…To improve the efficiency of the utilization of zinc resources, it is essential to focus on the development of technologies for the recovery of zinc-containing dust. Many investigations have reported that zinc ferrite could be decomposed by hightemperature roasting with the addition of lime [29,[35][36][37]. The recovery of zinc from synthetic zinc ferrite by calcium roasting and ammonia leaching was reported in our previous paper [38].…”
Section: Introductionmentioning
confidence: 81%
“…The following pyrometallurgical processes are or have been in operation to treat EAF dust: Rotary kiln (Waelz kiln), Rotary Hearth Furnace (RHF), Multi-stage furnace (PRIMUS), and the Electric Smelting Reduction Furnace (ESRF) [47]. 80-90% of the EAF dust which is recycled (approximately 2-2.1 Mt) is treated using the Waelz kiln, or a derivate of this technology, as it is currently deemed the most efficient processing route [42,44,48].…”
Section: Review Of Waelz Kiln For Eaf Dust Recycling and Carbon Footp...mentioning
confidence: 99%
“…Pretreatment and leaching of ferrous dusts-As discussed in the preceding sections, the presence of the refractory ZnFe 2 O 4 spinel presents challenges to the conventional leaching of these materials in aqueous media. As such, several studies have focused on the thermal pretreatment of Zn-bearing dusts before the leaching process (Chairaksa-Fujimoto et al, 2015;Miki et al, 2016;Chairaksa-Fujimoto et al, 2016;Yakornov et al, 2017). Chairaksa-Fujimoto et al (2015) investigated the effect of CaO addition on the conversion of ZnFe 2 O 4 in industrial EAF dust.…”
Section: Pgm Smelter Andmentioning
confidence: 99%